Multiple sclerosis and pregnancy. (May 2013) - Picardo, Elisa; Canuto, Emilie Marion; Marozio, Luca; Benedetto, Chiara
Multiple sclerosis (MS) is a chronic autoimmune disease of the CNS, which usually affects women during their childbearing years. Several studies have reported that pregnant MS patients have a low risk of disease progression and an even lower risk of exacerbation, especially in the third trimester, with a rise in relapse rate during the first 3 postpartum months. Although it has been demonstrated that pregnancy has no effect either on the lifetime course of the disease or long-term disability, it is not yet known exactly how well informed patients are as to the interactions between pregnancy and MS or how patients perceive the course of the disease during and after pregnancy. The heterogeneity of symptoms and their multifactorial impact on various sectors such as physical, psychological, familial, social and business necessitate the involvement of an interdisciplinary team with various professionals who work both with one another as well as with the MS patient. This article aims at providing the gynecologist with a brief overview of the most commonly encountered questions and situations to be faced when managing a pregnant woman with MS.